THE BARONG LANDUNG PERFORMING ART FROM THE PERSPECTIVE OF CULTURAL ACCULTURATION - Cerita, I Nyoman; Wirawan, AA Bagus; Suarka, I Nyoman (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2017)
The Barong Landung performing art, as the acculturation of the Balinese culture and Chinese culture, has opened the new history of the relationship between the Balinese culture and Chinese culture. The acculturation has also become the peak of the Chinese cultural impact on the Balinese culture in general and the Balinese performing art in particular. Moreover, Balong Landung has also been considered the symbolic appearance of the Balinese King, Sri Aji Jaya Pangus, and his wife, Kang Cing Wie, who governed from 1099 to 1103 Caka Year. The qualitative method was used in the present study and the data were collected through library research. The data were collected through the secondary data source. The primary data were collected through interview, observation, and documentation techniques. The result of the study shows that the barong landung performing art is a traditional Balinese performing art which has been affected by the Chinese culture. It has been strongly integrated into the elements of the people’s performing art and culture in every region of Bali. In Bali it reflects the humanity-oriented culture. It can be classified as the sacred, magical, and religious performing art and is performed as part of the traditional and religious rituals in Bali.